Tunable bandgap and spin-orbit coupling by composition control of MoS2 and MoOx (x = 2 and 3) thin film compounds. (15th May 2017) - Erfanifam, S.; Mohseni, S.M.; Jamilpanah, L.; Mohammadbeigi, M.; Sangpour, P.; Hosseini, S.A.; Iraji Zad, A.
Abstract: We report on the MoS2 and MoO x (x = 2 and 3) composite thin layers, electrodeposited, onto a Florine doped Tin Oxide (FTO) substrate. Our results show a change in relative content of these compounds in different thicknesses ranging from ∼20 to 540 nm. This change in the relative content at different thicknesses leads to a change in optical and electrical properties including bandgap and the type of semiconductivity. A sharp transition from p to n-type of semiconductivity is observed by scanning tunneling spectroscopy measurements. We find that the spin-orbit interaction of Mo 3d electrons in the MoS2 and MoO3 enhances by significant reduction of the MoO3 content in thicker layers. Graphical Abstract: Highlights: A composite form of MoS2, MoO2 and MoO3 thin film was electrodeposited. The relative content of these compounds was changed in different thickness of the layers. The bandgap and type of semiconductivity were tuned by change on the composition. Spin-orbit coupling of Mo 3d doublet was enhanced by composition control.